Strong-acid-enhanced polyacrylic acid hydrogel containing scleroglucan - Yuan Feng; Bin Chen; Mingmin Zhang; Rui Cheng; Xin Su; Yujun Feng (Materials & Design)
The practical application of polyacrylic acid (PAA) hydrogels is limited by inadequate mechanical performance, necessitating innovative enhancement strategies. A synergistic enhancement approach was developed, integrating scleroglucan (SC) within PAA networks and employing sulfuric acid (SA) treatment. Dual-network hydrogels (DN-gel) prepared via UV polymerization underwent two enhancement protocols: direct SA treatment, yielding sulfuric acid-based hydrogels (S-gel), and freeze-drying then SA treatment, producing freeze-dried sulfuric acid-based hydrogels (FS-gel). Experimental results demonstrated that DN-gel achieved a tensile strength of 0.12 MPa due to hydrogen bonding between SC hydroxyl groups and PAA carboxyl groups. S-gel exhibited simultaneous enhancements in strength (0.81 MPa) and elongation (1030 %). FS-gel attained a tensile strength of 2.6 MPa with reduced ductility, making it ideal for applications requiring structural rigidity. The SC and SA synergistic system facilitated multidimensional mechanical optimization of PAA hydrogels. This approach addresses the limitations of single-method enhancement and establishes novel design principles for high-performance hydrogel engineering.